2018
DOI: 10.1177/0047287518759227
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Directions in Tourism and Positive Psychology

Abstract: In recent years, tourism and positive psychology has developed as a humanist-inspired study of individual flourishing in tourism. This conceptual article aims to elaborate on epistemological foundations of tourism and positive psychology research and presents an overview of current trends and future directions for this field. The rapid rise of positive psychology within and outside tourism studies is analyzed, noting similarities and tensions between positive psychology and its predecessor, humanistic psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 89 publications
(111 reference statements)
2
59
0
1
Order By: Relevance
“…This is a heavily studied field, with several recent reviews ( Pyke, Hartwell, Blake, & Hemingway, 2016 ; Smith & Diekmann, 2017 ; Uysal et al, 2016 ). There is also a parallel but more prescriptive field known as positive psychology ( Coghlan, 2015 ; Filep & Laing, 2019 ; Nawijn & Filep, 2016 ; Vada et al, 2020 ). All this research has focussed on healthy individuals, not medical patients.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…This is a heavily studied field, with several recent reviews ( Pyke, Hartwell, Blake, & Hemingway, 2016 ; Smith & Diekmann, 2017 ; Uysal et al, 2016 ). There is also a parallel but more prescriptive field known as positive psychology ( Coghlan, 2015 ; Filep & Laing, 2019 ; Nawijn & Filep, 2016 ; Vada et al, 2020 ). All this research has focussed on healthy individuals, not medical patients.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Novelty is considered to be intricately connected to the experience of pleasure through experiences of flow, mindfulness, and creativity (Csikszentmihalyi, 1997;Filep et al, 2016). Novelty is related to emotional arousal through the alleviation of boredom and hedonic and eudemonic well-being (Iso-Ahola and Weissinger, 1990;Filep and Laing, 2019;Vada et al, 2019).…”
Section: Defining Noveltymentioning
confidence: 99%
“…This example of comparison only focuses on the scenarios with positive emotions, and on the other hand, if we look at the situations when negative emotions dominate: which groups of people are more likely to feel the best about their vacation-those experiencing only one type of emotion (e.g., three moments of fear) or those experiencing a mixture of emotions (e.g., one moment of fear, one moment of guilt, and one moment of sadness)? Prior research has shown that high levels of positive emotion and low levels of negative emotion contribute to individuals' well-being (Diener et al 1999;Filep and Laing 2019;Fredrickson 2001). If well-being is the result of simple arithmetic addition, no matter in the first or the second comparison, the two groups of tourists should achieve the same level of well-being because they experience the same amount of positive emotions and negative emotions.…”
Section: Introductionmentioning
confidence: 99%